Review Article: Pharmacological Activities and Bioactive Compounds of Toona sinensis as a Potential Herbal Medicine - Oktariani, Anisa; Muhaimin, Muhaimin (Pendidikan Kimia FKIP Universitas Jambi, 2025)
Indonesia is rich in natural resources, one of which is Toona sinensis, a plant from the Meliaceae family known to contain various bioactive compounds. This study aims to summarize the pharmacological activities of Toona sinensis as well as the bioactive compounds it contains. A literature review approach was used, referencing various studies that report on the antioxidant, anticancer, antidiabetic, anti-inflammatory, and antigout activities of this plant. Several bioactive compounds such as polyphenols, flavonoids, terpenoids, and limonoids have been identified as the main components contributing to its pharmacological effects. The results of the study indicate that Toona sinensis has significant potential as a natural source of medicine for various diseases. The implications of these findings could lead to the development of plant-based drugs for the treatment of various diseases and enhance the knowledge of medicinal plants in Indonesia. Keywords: Anticancer, antioxidant, bioactive compounds, pharmacological activities, Toona sinensis.